Notes on Early Land Plants Today. 16. Validation of Metahygrobiella subgen. Apohygrobiella (Cephaloziaceae, Marchantiophyta) - Váňa, Jiří; Söderström, Lars; Hagborg, Anders; Von Konrat, Matt (Phytotaxa, 2013)
Schuster (2002) classified the genus Metahygrobiella Schuster (1961: 205) into two subgenera but failed to validate the subgenus Apohygrobiella.